Principles Of Russian Orthography (Global Scientific Review, 2025)
This article examines two of the four main principles of Russian orthography - morphological and phonemic. The relevance of the description of the principles of orthography is determined by the importance of the object of consideration: the principles of orthography constitute one of the main links in the writing system as a whole. And the morphological, or phonemic principle is recognized by the overwhelming majority of linguists as the leading principle of Russian orthography